The last kids on earth and the midnight blade ebook - Brallier, Max (Last Kids on Earth, 2019)
Now a Netflix original series! The fifth book in the New York Times , USA Today , and Wall Street Journal bestselling series, with over 7 million copies in print! "Terrifyingly fun! Delivers big thrills and even bigger laughs."—Jeff Kinney, author of the #1 New York Times bestseller Diary of a Wimpy Kid The 5th book of the New York Times bestselling series! Surviving their first winter after the Monster Apocalypse was no easy feat, yet Jack and his buddies waste no time springing to action against some of the nastiest, most evil monsters around. When Jack discovers his Louisville Slicer has new, otherworldly powers, he's thrown into epic training to find out what kind of destruction the blade can wield. But between fighting off zombies, fleeing from strange, glowy Vine-Thingies erupting from the ground, and squeezing in a video game session or two, there's barely time left to figure out what's wrong with their buddy, Dirk, who's been acting weird any time he's around the undead. When an unexpected villain appears, can Jack and his friends save themselves—and the rest of the world—from cosmic domination? Note: most illustrations are printed in black-and-white, with the occasional gray-and-white image.